Financial development and economic growth in Asian countries: evidence from the DCCE approach - Wang, Yujue; Mazlan, Nur Syazwani; Wan Ngah, Wan Azman Saini; Faheem, Muhammad (Springer Science and Business Media Deutschland, 2024)
Asia has constantly been in the spotlight regarding economic development as it has been the fastest-growing global region over recent decades. This study investigated the effect of financial development on economic growth in selected Asian countries at various stages of economic development. A recently introduced approach, the Dynamic Common Correlated Effects (DCCE) method, was applied to 12 Asian countries/areas covering 26 years (1995–2020). The 12 countries/areas were divided into three groups based on their current economic development status: underdeveloped, moderately, and highly developed. The study results indicated that the effect of financial development on economic growth varied for countries at different economic levels. The association between financial development and economic growth was strongly negative for underdeveloped countries. However, a positive relationship existed between the sampled moderately and highly developed countries/areas. This situation implied that financial development should not be considered a viable way to boost economic growth for countries with underdeveloped economies. Instead, countries with a higher economic status should priorities financial development to promote economic prosperity effectively.